Pengembangan Alat Braille Alphabet Sounds untuk Mengenalkan Konsep Huruf Abjad Pada Anak Disabilitas Netra - Rahmadhania, Laurina; Taufan, Johandri (Universitas Negeri Padang, 2024)
This research is motivated by the problems faced by children with total visual disabilities in memorizing Braille alphabet letters in the form of dots. To overcome this problem, researchers developed Braille Alphabet Sounds which aims to introduce blind children to the concept of alphabet letters by utilizing the senses of hearing and touch. This tool is designed to help blind children learn alphabet letters through a combination of learning from Braille letters and sounds. The research method used is the Borg and Gall development method which consists of ten steps and then modified into five research steps. The developed product was validated by several experts including electronics experts, blind disability experts, and media experts as well as practicality conducted by blind disability teachers at SLB Wacana Asih Padang and SLBN 2 Padang. The results of trials by several related experts, as a whole, obtained a score with a percentage of 82% which was categorized as very valid. While the results of the practicality test by the teacher obtained were 94% with a very practical category. Thus, the results of the validation test and practicality test carried out, there are inputs and suggestions from experts so that the Braille Alphabet Sounds tool can be used in recognizing alphabet letters in children with visual disabilities